La derivación de las causas de alimentos al Centro de Mediación del Concejo de la Judicatura de la ciudad de Riobamba y su incidencia en la solución alternativa de conflictos durante el período agosto 2014- febrero del 2015 - Rivadeneira Torres, Iván Francisco (2015)
This research work disclosed as legal effect because the testimony of the expert recognition scene in the judgments issued in the First Court of Morona Santiago Transit during the period 2012-2013. The structure of this research is divided into five chapters: the first chapter deals with the guiding framework where the problem statement, originates its origin, as presented and how it behaves, after which formulated the general objective and specific objectives to determine whether legal effects because the testimony of the expert in the recognition scene in the judgments delivered by the Court of First Transit Morona Santiago, and the rationale and importance of the problem where we see that This research work is feasible, new and original. In the second chapter, the theoretical framework is developed, with the background, theoretical foundation based on my research, the instrument of the signing was applied through which doctrine, theories, concepts and bibliographic articles from codes, books, laws was obtained , regulations and texts it comes to build the theoretical, conceptual, legal and doctrinal part of the research, this chapter is divided into four units, with its subunits; in the first unit talk about the criminal background traffic, the history of criminal proceedings transit, definition, characteristics, procedure, stages, due process rights, the criminal proceedings, the judgment; in the second unit will talk about the expert in criminal proceedings transit, with definition of expert is the expert in criminal proceedings transit importance of the expert, prejudicialidad the report, its contents, responsibility, status, class expertise, merit of the expert evidence, requirements; in the third unit will talk about expert evidence in crimes of transit, origin of expert evidence, expert witness in criminal proceedings, the subject of expert evidence, expert evidence guarantees, the testimony of the expert, the importance of expert testimony and comparative law; in the fourth unit we will talk about the legal effects in judgments acquittal, ratification of innocence, compensation, analysis of trials, hypothetical unit, hypotheses, variables, operationalization of variables. In the third chapter, we will develop the methodological framework, through the scientific method, we turn to the implementation of the research through research surveys the implementation of the legal profession and interviews for the Lord Chief Justice Morona Transit Santiago, as well as Messrs experts accredited by the judiciary of Morona Santiago, this in order to get to establish whether caused legal effect the testimony of the expert recognition scene in the judgments, the interview guide with inductive and analytical method; through the interview and the inductive method I could get the information that helped me identify somehow the legal effect which brings the testimony of the expert in the recognition scene in the judgments on the other hand applying the analytical method and reach a critical legal analysis and to verify the hypothesis. In the fourth chapter, the conclusions and recommendations obtained from research through interpretation and discussion of the results achieved in the statistical tables and charts, with the help of EXCEL software package in which results are obtained in exact percentages set for data processing, which is why this research is descriptive because after tabulate, interpret and process information, described the problem as it appears, behaving in its explanatory context, the result then tabulated and calculated; Finally in the fifth chapter the literature, supplementary literature, internet sources and Annexes.